2015
DOI: 10.1002/2014wr015997
|View full text |Cite
|
Sign up to set email alerts
|

Does improved SSTA prediction ensure better seasonal rainfall forecasts?

Abstract: Seasonal rainfall forecasts in Australia are issued based on concurrent sea surface temperature anomalies (SSTAs) using a Bayesian model averaging (BMA) approach. The SSTA fields are derived from the Predictive Ocean-Atmosphere Model for Australia (POAMA) initialized in the preceding season. This study investigates the merits of the rainfall forecasted using POAMA SSTAs in contrast to that forecasted using a multimodel combination of SSTAs derived using five existing models. In addition, seasonal rainfall fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
(65 reference statements)
0
19
0
Order By: Relevance
“…The procedure followed is outlined below. Read observed and modelled seasonal SSTA forecasts over the entire global SST grid. At each grid point, calculate the seasonal forecast errors of both the models over the calibration period by subtracting the ensemble mean of the model forecast from the observed seasonal SSTA. In order to have sufficient sample size for a fair assessment of model weights, consider a moving window of 2 years for model 2 and augment the number of data points by considering eight nearest grid points around the target grid cell Khan et al . (). The procedure provides 22 events over the calibration period. Model 2 (ECMWF) now has forecast errors for each 2 years period (e.g., 1960–1961, 1961–1962, …, 1981–1982) which moves forwards within the calibration period, while model 1 (MF) has forecast errors for the entire calibration period.…”
Section: Application Of Model and Results Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure followed is outlined below. Read observed and modelled seasonal SSTA forecasts over the entire global SST grid. At each grid point, calculate the seasonal forecast errors of both the models over the calibration period by subtracting the ensemble mean of the model forecast from the observed seasonal SSTA. In order to have sufficient sample size for a fair assessment of model weights, consider a moving window of 2 years for model 2 and augment the number of data points by considering eight nearest grid points around the target grid cell Khan et al . (). The procedure provides 22 events over the calibration period. Model 2 (ECMWF) now has forecast errors for each 2 years period (e.g., 1960–1961, 1961–1962, …, 1981–1982) which moves forwards within the calibration period, while model 1 (MF) has forecast errors for the entire calibration period.…”
Section: Application Of Model and Results Discussionmentioning
confidence: 99%
“…The approach developed to combine multi‐model forecasts of unequal time periods follows the model weighting scheme of Khan et al . (). In this scheme, the weight of an individual model is derived from the dependence structure of model forecast errors defined in terms of a covariance matrix using a common time periods of data across all the models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in case of seasonal SSTA predictions, the multimodel forecasts show clear improvement over a single model prediction around the globe irrespective of seasons. Khan et al [] also showed that the multimodel SSTA forecasts offers consistent and significant improvements for all the seasons over the most of grid cells than any other approach.…”
Section: Resultsmentioning
confidence: 99%
“…BJP has 20 since been applied to calibrate hourly rainfall forecasts (Shrestha et al, 2015;Robertson et al, 2013b) and seasonal rainfall forecasts (Hawthorne et al, 2013;Khan et al, 2015;Peng et al, 2014;. BJP was most recently adapted for sub-seasonal to seasonal streamflow forecasting Schepen et al, 2016).…”
Section: Bayesian Joint Probability Modelsmentioning
confidence: 99%